Inhibitory control over Ca(2+) sparks via mechanosensitive channels is disrupted in dystrophin deficient muscle but restored by mini-dystrophin expression. - Teichmann, Martin D. H.; von Wegner, Frederic; Fink, Rainer; Chamberlain, Jeffrey S.; Launikonis, Bradley S.; Martinac, Boris; Friedrich, Oliver (PLoS ONE, 2008)
BACKGROUND In dystrophic skeletal muscle, osmotic stimuli somehow relieve inhibitory control of dihydropyridine receptors (DHPR) on spontaneous sarcoplasmic reticulum elementary Ca(2+) release events (ECRE) in high Ca(2+) external environments. Such 'uncontrolled' Ca(2+) sparks were suggested to act as dystrophic signals. They may be related to mechanosensitive pathways but the mechanisms are elusive. Also, it is not known whether truncated dystrophins can correct the dystrophic disinhibition. METHODOLOGY/PRINCIPAL FINDINGS We recorded ECRE activity in single intact fibers from adult wt, mdx and mini-dystrophin expressing mice (MinD) under resting isotonic conditions and following hyper-/hypo-osmolar external shock using confocal microscopy and imaging techniques. Isotonic ECRE frequencies were small in wt and MinD fibers, but were markedly increased in mdx fibers. Osmotic challenge dramatically increased ECRE activity in mdx fibers. Sustained osmotic challenge induced marked exponential ECRE activity adaptation that was three times faster in mdx compared to wt and MinD fibers. Rising external Ca(2+) concentrations amplified osmotic ECRE responses. The eliminated ECRE suppression in intact osmotically stressed mdx fibers was completely and reversibly resuscitated by streptomycine (200 microM), spider peptide GsMTx-4 (5 microM) and Gd(3+) (20 microM) that block unspecific, specific cationic and Ca(2+) selective mechanosensitive channels (MsC), respectively. ECRE morphology was not substantially altered by membrane stress. During hyperosmotic challenge, membrane potentials were polarised and a putative depolarisation through aberrant MsC negligible excluding direct activation of ECRE through tubular depolarisation. CONCLUSIONS/SIGNIFICANCE Dystrophin suppresses spontaneous ECRE activity by control of mechanosensitive pathways which are suggested to interact with the inhibitory DHPR loop to the ryanodine receptor. MsC-related disinhibition prevails in dystrophic muscle and can be resuscitated by transgenic mini-dystrophin expression. Our results have important implications for the pathophysiology of DMD where abnormal MsC in dystrophic muscle confer disruption of microdomain Ca(2+) homeostasis. MsC blockers should have considerable therapeutic potential if more muscle specific compounds can be found.